To assess and create awareness among anesthetists regarding prevention and management of injuries to the teeth and their associated structures during general anesthesia - Amita M Tiku; Rahul J Hegde; Lipika A Swain; Falguni R Shah (Wolters Kluwer Medknow Publications, 2014)
Aims: The aim of this study was to assess the awareness among anesthetists regarding prevention and management of injuries to the teeth and their associated structures during anesthesia. Study design, Materials and Methods: Fifty anesthetists practicing in various hospitals in Mumbai participated in this study. A questionnaire was devised and distributed among them. The completion of the questionnaire by the respondents was taken as their consent to participate in the study. Statistical analysis: The data thus collected was analyzed using statistical package Medcalc (Version 12.7.0.0). Results: The results showed that the injury to the oro-dental tissues is a common finding during anesthesia. The maxillary incisors underwent injuries more commonly than the mandibular incisors. Padding of the teeth was the most common precaution taken to prevent injuries to the teeth which, however, is not adequate. The management for such injuries was inadequate and in many cases, the patients' referral to a dentist was not considered post-operatively. Conclusion: Pediatric dentists can play a major role in creating the awareness among the anesthesia providers regarding prevention of oro-dental injuries during anesthesia.